Philippine Army Finance Center Producers Integrated Cooperative A case study on democratization and development. - Arcales, Sherry Mae A. (Sherry Mae A. Arcales, 2009)
For the past decades, cooperatives have been the primary engines of development and democratization, not just in the Philippines, but also in other parts of the globe. Through their various services and programs, these organizations bring about economic and political empowerment to the people in the community in which they are located.